Hyper-reactive mononuclear cells and neutrophils in chronic periodontitis - A. Gustafsson (Blackwell Synergy, 2006)
Objectives: Stimulated mono- and polymorphonuclear cells from patients with periodontitis have shown increased release of interleukin-1b (IL-1b) and oxygen radicals, respectively. The aim was to study whether this hyper-reactivity could be found both in mono- and polymorphonuclear cells from the same patient, and whether there was a relation to the gene coding for IL-1b (IL-1b13953). Material and Methods: Peripheral mononuclear cells from 14 non-smoking and well-treated patients and pair-matched controls were incubated with opsonized Staphylococcus aureus and lipopolysaccharide (LPS). Released IL-1b and tumour necrosis factor (TNF)-a were determined with ELISA. Generation of oxygen radicals from the Fcg-receptor-stimulated neutrophils was measured with chemiluminescence and the polymorphism at IL-1b13953 was measured with polymerase chainreaction. Results: The mononuclear cells from the patients released more IL-1b after incubation with LPS (po0.001) and with bacteria (po0.05). The release of TNF-a tended to be higher in the patient group. The peripheral neutrophils from the patients generated more oxygen radicals (po0.06). We found no differences between the study groups regarding the IL-1b13953 polymorphism. Conclusion: The similarity in systemic inflammation between patients and controls suggests that the increased release/generation of IL-1b and oxygen radicals from peripheral leukocytes in periodontitis patients is of a constitutional nature and of pathogenic relevance.